Colour Stability and Lipid Oxidation of Beef Longissimus Lumborum under Different Packaging Conditions - Bonny Dadji Stéphane Serge (Polish Journal of Food and Nutrition Sciences, 2017)
The objective of this study was to investigate the colour stability and lipid oxidation of beef under different packaging methods. The muscles longissimus lumborum were randomly packed in vacuum or modified atmosphere packaging (MAP, 80% O2, 20% CO2). Both packages were aged at 4°C for 7, 14 and 21 days. After each ageing time, samples were displayed in a refrigerator for 2, 4 and 6 days. Colour stability, lipid oxidation and their correlation were determined. Beef under vacuum packaging showed higher a* values on 7, 14, and 21 days of ageing and lower L* values on 14 and 21 days of ageing than beef in MAP (p<0.05). Lower a* values were observed in the samples packed in MAP, then displayed compared to samples packed in vacuum, then displayed after 21 days of ageing time on day 2, 4 and 6 of the display period (p<0.05). Thiobarbituric acid reactive substances (TBARS) increased significantly in MAP compared to vacuum during 7, 14, and 21 days of ageing (p<0.05). An increase of TBARS was also observed during display after 14 and 21 days of ageing in samples packed in MAP, then displayed. Furthermore, a significant difference (p<0.05) was observed between samples packed in MAP and vacuum in peroxide value on 14 days of ageing. Lipid oxidation was observed mainly in the samples packed in MAP compared to vacuum, and positively correlated with results on colour stability.